(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The aim of the current study is to examine the impact of the ogive radius of a 7.62x39 ammunition projectile on the positioning of a radially-slotted channel that helps increase the angle of the cavitation cavity. The studies were conducted using CFD (Computational Fluid Dynamics) analyses in a SolidWorks environment, simulating the projectile's movement in a water environment. The research findings indicate that lower values of the ogive radius result in higher values of the cavitation cavity angle, which in turn suggests that lower values are more favorable for creating bullets with slotted channels, which enhances linear-progressive movement in a water environment and thus increases the chance of hitting targets below sea level.